Designing and evaluating social safety nets: theory, evidence, and policy conclusions - Coady, David (International Food Policy Research Institute, 2004)
This paper reviews the literature on the performance of commonly found social safety net programs in developing countries. The evidence suggests that universal food subsidies have very limited potential for redistributing income. While targeted food subsidies have greater potential, this can only be realized when adequate attention is given to the design and implementation, as well as to the social and political factors influencing the adoption, of these programs. Although well-designed public works programs have impressive targeting performance, they have large non-wage costs; thus, to be cost-effective, they need to produce outputs that are especially beneficial to poor households. Social funds, which emphasize both community involvement and asset creation, have been cost-effective, but they are difficult to target to extremely poor households. Traditional public works programs are particularly attractive for addressing vulnerability, but they require flexibility regarding choice of output. Targeted human capital subsidies appear to have great potential for addressing extreme poverty; but again, their design needs to reflect the human capital profile of countries and the administrative capability of the government. -- Author's Abstract